The Derivation of Silica from Coconut Husk Ash: Preliminary Study - Nasrudin, Nurul Nazaitul Nabila; Mohd Rodzi, Nursyaqeena Saffiya; Ismail, Nurul Afifah; Roslan, Muhammad Sufi (Multidisciplinary Applied Research and Innovation, 2025)
Coconut husk is widely known as agricultural waste that can be burned and transformed into coconut husk ash (CHA). Conversion coconut husk into an ash  becomes an environmentally alternative by turning the waste to resources. This wastes can give a bad impact to the environment if  managed in the wrong way because it can release gaseous to the atmosphere.  But, this project  aims at different chemical treatments  by using acid treatment and alkali treatment to produce silica by using coconut husk ash. The silica will be going through the characterization by using Fourier-transform Infrared Spectroscopy (FT-IR) and Field Emission Scanning Electron Microscope (FESEM). Silica obtained is easier to produce and more environmentally friendly. Silica is important in this country because it can be used in an industry as a catalyst, construction and many more.